2018
DOI: 10.1111/ijlh.12782
|View full text |Cite
|
Sign up to set email alerts
|

The utility of bone marrow sampling in the diagnosis and staging of lymphoma in South Africa

Abstract: In the South African public sector, high HIV prevalence leads to a different lymphoma pathology profile from the developed world. High BMI rates are encountered. Here, and in similar resource-constrained settings, international lymphoma staging guidelines can be logistically challenging and unaffordable. BMB remains useful in the staging and diagnosis of lymphoma. Unilateral sampling with a processed trephine length of at least 26 mm is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Infection with HIV-1 is associated with the development of multiple cancers. Amongst these, the highly aggressive B-cell lymphoma BL is particularly over-represented among the HIV positive population, of which Sub-Saharan Africa has one of the highest incidences in the world ( Abayomi et al, 2011 ; Phillips and Opie, 2018 ). Recent studies have brought attention to the oncogenic potential of HIV-1 and its associated proteins in promoting these cancers, and the molecular mechanism driving these phenomena is still poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with HIV-1 is associated with the development of multiple cancers. Amongst these, the highly aggressive B-cell lymphoma BL is particularly over-represented among the HIV positive population, of which Sub-Saharan Africa has one of the highest incidences in the world ( Abayomi et al, 2011 ; Phillips and Opie, 2018 ). Recent studies have brought attention to the oncogenic potential of HIV-1 and its associated proteins in promoting these cancers, and the molecular mechanism driving these phenomena is still poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies addressing the role of bone marrow examination in the diagnosis of lymphoma, including the literature extracted for this guideline, did not directly address the primary diagnosis of lymphoma in general. The 3 studies [39][40][41] outlined exemplify the most common study objectives: incidence of bone marrow involvement at primary diagnosis in the context of staging procedures of 1215 patients, 40 comparison of diagnostic yield of aspirate versus biopsy in 143 lymphoma patients, 39 and the diagnostic accuracy of bone marrow examination versus tissue sampling for the diagnosis of splenic marginal zone lymphoma and splenic diffuse red pulp small B-cell lymphoma, comparing immunophenotype and classification on bone marrow biopsies and splenectomy specimens. 41 It is self-evident that bone marrow examination is the diagnostic modality of choice in lymphomas that may only involve bone marrow and no other sites, such as LPL.…”
Section: Strong Recommendation-clinical Care Providersmentioning
confidence: 99%
“…39 Discordant bone marrow involvement by low-grade lymphoma and other tissue involvement by high-grade lymphoma was infrequently reported at 4.8%, and discordant high-grade bone marrow transformation with low-grade tissue involvement was reported at 4.5%. 40 The evidence base supporting this recommendation comprised 3 studies. [39][40][41] All 3 studies had an RCS design and were assessed as low 39,41 or very low 40 quality.…”
Section: Strong Recommendation-clinical Care Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…4 More recently in 2018, in a study conducted by Philips and Opie to assess the use of bone marrow examination in lymphoma sufferers in South Africa, it was shown that out of the 1215 Bone marrow aspiration and trephine (BMAT) records, bone marrow involvement was most commonly present in non-Hodgkin's lymphoma (43.7%), followed by high-grade B subtypes (28.9%) and Hodgkin's lymphoma (35.7%). 5 Background: Bone marrow aspiration and trephine biopsy (BMAT) are widely performed in adults to evaluate haematological and malignant conditions. However, the diagnostic yield from the procedure in unselected patients in the South African public sector has not previously been described.…”
Section: Introductionmentioning
confidence: 99%